The Oil That Lasted a Thousand Years - Scolnic, Benjamin (Zutot, 2024)
Abstract While the familiar Hanukkah story of the ‘miracle of the oil’ is often dismissed as quaint and fanciful, it may be seen as a final link in an interesting chain of traditions about the sanctity of Judaism’s holiest of places. In the book of Exodus, one type of oil is used to light the lamps and another oil is used to anoint the Tabernacle and make it inviolate. The Tabernacle became part of the First Temple so there was no need to anoint the Holy of Holies there. In the time of the First Temple, some considered the Temple to be inviolate. When the First Temple was destroyed, no aspect of the new Temple was anointed. In the 160s BCE, during the Antiochene persecution, some felt the need to explain how the Temple could have been violated. The author of Daniel 9 reinterpreted Jeremiah’s prophecies of the 70 years of exile to be 70 weeks of years so that everything that had befallen the Judeans was seen as part of God’s overarching plan. The complex issues of continuity/discontinuity between, and the violability/inviolability of the temples, underlie Dan. 9 and related texts.
Keywords: Book of Daniel; Hanukkah; Jeremian prophecies; continuity/discontinuity; dept.jst; oil; peer-reviewed; temples